2009
DOI: 10.1007/s10495-008-0301-y
|View full text |Cite
|
Sign up to set email alerts
|

Cell death: protein misfolding and neurodegenerative diseases

Abstract: Several chronic neurodegenerative disorders manifest deposits of misfolded or aggregated proteins. Genetic mutations are the root cause for protein misfolding in rare families, but the majority of patients have sporadic forms possibly related to environmental factors. In some cases, the ubiquitin-proteasome system or molecular chaperones can prevent accumulation of aberrantly folded proteins. Recent studies suggest that generation of excessive nitric oxide (NO) and reactive oxygen species (ROS), in part due to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
104
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(109 citation statements)
references
References 172 publications
0
104
0
Order By: Relevance
“…S8). In relation to this scenario, our study is under way to clarify a possible regulatory role of CIB1 in the activation of ASK1-JNK signaling processes initiated by NMDA signaling, which triggers both Ca 2ϩ influx and ROS production in neurons in the brain (31).…”
Section: Discussionmentioning
confidence: 99%
“…S8). In relation to this scenario, our study is under way to clarify a possible regulatory role of CIB1 in the activation of ASK1-JNK signaling processes initiated by NMDA signaling, which triggers both Ca 2ϩ influx and ROS production in neurons in the brain (31).…”
Section: Discussionmentioning
confidence: 99%
“…55 The current study showed that the expression of ER stress markers GRP78 (protein and mRNA) and c-Jun mRNA increased significantly in the MCDD group, whereas the expression of all of them decreased markedly after changing the diet. Another ER stress-related molecule, PDI, 30,31 showed similar behavior (Figure 6d and e). Thus, ER stress may be a key factor in MCDD-induced fatty liver fibrosis.…”
Section: Discussionmentioning
confidence: 63%
“…In addition, PDI, an ER-residing protein that catalyzes protein folding and thiol-disulfide interchange reactions, 30,31 was markedly induced in group M compared with groups C and R (Figure 6d). …”
Section: Involvement Of Er Stress In Fibrosis Of Steatohepatitis and mentioning
confidence: 99%
“…Notably, NOS activation may increase the production of the rate-limiting enzyme for glutathione synthesis and of genes involved in antioxidant defence [41]. Similarly, NO has a dual role in the regulation of neuronal cell survival, being neuroprotective through Snitrosylation of NMDA receptors, and yet neurodestructive by the formation of peroxynitrite [42]. The dual role of NO in the regulation of beta cell survival is also demonstrated by its opposite effects on ER stress.…”
Section: Discussionmentioning
confidence: 99%